v - Parvathi Nagesha; Anto Aparna; Ittigi Vivekananda; Rangegowda Suresh; Rangaswami Umadevi (Our Dermatology Online, 2021)
Background: Skin lightening products (SLP) are widely used cosmetics among people that may result in lightening of skin complexion and may damage the skin. There seems to be a strong demand for lighter skin tone that is shared globally and promoted by the media. Aims and Objectives: To investigate the knowledge, attitude, and use of SLPs and its social and psychological correlation among people in a south Karnataka district Materials and Methods: A cross sectional survey, 2000 individuals irrespective of age and sex from a district in south Karnataka responded to a questionnaire. Results: This study explored SLPs use among 2000 individuals irrespective of age and sex in Hassan, Karnataka using a questionnaire. A total of 33.8% of the sample reported currently using SLPs, with women being two times more likely using these products. Among current users, 12.8% reported past experiences of adverse side effects. "Friends" and "Family" were the most common influence for using fairness products, followed by "Advertisements". Discussion: Cosmetics market is flooded with skin lightening products and rampant use of the same has become a major public health concern in all countries along with the reinforcement of racism and social disparities. Side effects for skin lightening products are less reported which is similar to other studies. This could be the reason why there is no regulation of the products or the ingredients in the products. Conclusion: A high prevalence of SLP use was found in a sample of population in south Karnataka, and several social and mental health-related risk factors were found that may help in guiding interventions.